Magnesium and its alloys as Biomaterial for bone repair: advances, challenges and future direction in mechanical and tissue engineering research - Jasmawati, Noor; Nafrizal; Zulhanif; Ibrahim, Fauzi; Sukmana, Irza (INSTEP Network, 2025)
Interest in the application of biodegradable bone screw is driven by the increasing knowledge on biomedical materials and tissue engineering field. Currently, various polymeric- as well as metallic-based materials have been used as degradable bone screw. Biodegradable material is a desirable feature for bone screw since the goal is that it uses as a temporary structure holding a growing bone tissues until the bone fracture has sufficiently healed. Among others, magnesium and its alloys have a potential chance to serve as biodegradable bone screw applications, as it has mechanical properties similar to natural bone, lightweight, and biocompatible approved. This article aims to report current development and future potential use of magnesium-based metal for bone screw application. Techniques on manufacturing process, mechanical performance, and biocompatibility assessment of magnesium and its alloys are highlighted.